Phenotypic T cell exhaustion in a murine model of bacterial infection in the setting of pre-existing malignancy. - Rohit Mittal (Public Library of Science (PLoS), 2014)
While much of cancer immunology research has focused on anti-tumor immunity both systemically and within the tumor microenvironment, little is known about the impact of pre-existing malignancy on pathogen-specific immune responses. Here, we sought to characterize the antigen-specific CD8+ T cell response following a bacterial infection in the setting of pre-existing pancreatic adenocarcinoma. Mice with established subcutaneous pancreatic adenocarcinomas were infected with Listeria monocytogenes, and antigen-specific CD8+ T cell responses were compared to those in control mice without cancer. While the kinetics and magnitude of antigen-specific CD8+ T cell expansion and accumulation was comparable between the cancer and non-cancer groups, bacterial antigen-specific CD8+ T cells and total CD4+ and CD8+ T cells in cancer mice exhibited increased expression of the coinhibitory receptors BTLA, PD-1, and 2B4. Furthermore, increased inhibitory receptor expression was associated with reduced IFN-γ and increased IL-2 production by bacterial antigen-specific CD8+ T cells in the cancer group. Taken together, these data suggest that cancer's immune suppressive effects are not limited to the tumor microenvironment, but that pre-existing malignancy induces phenotypic exhaustion in T cells by increasing expression of coinhibitory receptors and may impair pathogen-specific CD8+ T cell functionality and differentiation.